Role of Basti and Snehana Putapaka in the Management of Shushkaakshipaka with respect to Sjogren’s Syndrome (International Journal of Ayurveda and Pharma Research, 2024)
Sjogren’s syndrome is an autoimmune disorder in which the immune system attacks the glands that make moisture in the eyes, mouth, and other parts of the body. The triad of Sjogren’s syndrome consists of keratoconjunctivitis sicca (dry eye), xerostomia (dry mouth) and rheumatoid arthritis. From Ayurvedic perspective, the pathophysiology of Sjogren’s shows Vata dosha dushti leading to Sandhigata vikara, Roukshya and Shushkaakshipaka. Shushkaakshipaka is a Vata-pittaja, Sarvagata netra vikara that matches the clinical picture of dry eyes disease. To control this Prakupit vata dosha; Sanshodhan and Shaman both are required. As a result, Vata shodhana was achieved by Basti upakram and Basti pashchat Snehana Putapaka, Nasya and Snehapana brought about Vata shamana. Patient’s dryness of eyes was assessed using Schirmers test and Tear film Break up test. After treatment Schirmer’s reading showed significant improvement from 2mm to 10mm and from 4mm to 8mm in right and left eye respectively. Other symptoms of patient like dryness of mouth and joint pain also reduced to a certain amount. This case report shows a classical Ayurvedic treatment protocol used to treat Sjogren’s Syndrome.